The role of organizational climate, and work–family conflict in burnout: The case of teachers - Junça Silva, A.; Freire, M. (Sustainability, 2022)
Burnout is a major concern for the scientific and educational community, as it leads to harmful consequences, both at a personal and organizational level. Several studies showed that burnout is influenced by multiple factors, including organizational climate and work–family conflict. However, studies analyzing these three variables together in the educational sector are scarce. Thus, this study aimed to analyze whether the organizational climate influenced burnout through work–family conflict. We collected data in two-time points with 253 teachers. The results showed that only the organizational climate dimensions of involvement, control, autonomy, task orientation, and physical comfort were associated with burnout. Plus, only the physical comfort and autonomy climates significantly reduced burnout via the decreases in work–family conflict. Thus, these organizational climates’ dimensions seem to be essential factors to reduce not only work–family conflict but also burnout in the educational sector. This study tested the mediating role of work–family conflict on the link between organizational climate and burnout, with a group of teachers. Additionally, the data was collected during the pandemic crisis of COVID-19.